Analysis of The Effectiveness of KIP Scholarship Governance on Improving the Quality of Higher Education: (Case Study of UIN North Sumatra Students) - Novitri, Dian; Tarigan, Azhari Akmal; Dharma, Budi (Jurnal Manajemen Bisnis, 2024)
This study aims to determine the effectiveness of Kip scholarship governance at North Sumatra State Islamic University. The research method used is descriptive with a qualitative approach, the research was conducted at the Academic Bureau of UIN North Sumatra, the research sample was students who received Kip scholarships in 2019. Data analysis was carried out using the miles and huberman method which consists of data collection, data reduction, data presentation and conclusion drawing. The results showed that based on the effectiveness indicators, namely seen from the accuracy of the program targets that have been running effectively, the socialisation of the program has been declared appropriate, the supervision of the program has been said to be appropriate, but the indicators of achieving program objectives have not been fully effective. The effectiveness of governance in the implementation of the KIP scholarship programme at UIN North Sumatra is a policy implementation in supporting the government's commitment to provide access to higher education to people who have economic limitations. Therefore, further research is needed that focuses more on further supervision of the programme so that the objectives of the KIP programme can be achieved.